Web based expert system for diagnosing disease pest on banana plant - Budiyanto, Gunawan; Ipnuwati, Sri; Azam Al Gifari, Sayyid; Huda, Miftachul; Jalal, Burhanuddin; Abdul Latif, Aliza; Maseleno, Andino; Lia Hananto, April (International Journal of Engineering and Technology, 2018)
Development of computer technology inspires the creation of a computer application Expert System in Diagnosing Web-Based Banana Plant Disease. The purpose of this research was to create a computer application that could be used by laymen, either Banana farmer or the general public who wanted to know information about Ambon Banana plant. In this system, the number of the program provided would have given the significant contribution in building the program which may be useful for diagnosing pests and diseases in Banana plants. There were 37 symptoms that resulted in 5 diagnoses caused by pests, namely Leaf Rollers, Uret Beetles, Nematodes, Fruit Scabies and Aphids and produced 4 diagnoses caused by diseases, namely Fusarium Wilt, Bacterial / Blood Disease, Banana Dwarf and Leaf Spots. The programming language used in designing this Expert System was PHP. For data storage, the author used MySQL. The method used to determine the type of pest and disease, the author used fuzzy logic method. While to build this Expert System application, the author used a Web-based application that aimed to make its use wider, so that farmers / the general public do not have to consult with an expert simply by using this application. The results of this application, users will be given a solution about pests or diseases that attack the Ambon Banana plant and how to treat it so that it can overcome pests and diseases early.